2022
DOI: 10.1111/nyas.14782
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐talk of four types of RNA modification writers defines the immune microenvironment in severe asthma

Abstract: Adenine modifications, including m 6 A, m 1 A, APA, and A-to-I modifications, are the most impactful RNA modifications. These modifications are primarily produced by enzymes called writers. The main purpose of this study was to explore the cross-talk and potential roles of these writers in severe asthma. We found 13 RNA writers potentially related to severe asthma and three RNA modification patterns. Cluster 3 showed predominant neutrophil infiltration and C-type lectin receptor signaling; cluster 1 showed pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Studies had shown a strong connection between asthma and the immune microenvironment. 25 , 26 Consequently, we next used the GSE41861 database in the Cibersort package to predict the proportion of 22 immune infiltrating cells in the immune microenvironment of asthma. The results are shown in Figure 8A , the percentages of dendritic cells activated, plasma cells, T cells CD4 memory activated and mast cells activated in asthma were higher than controls, while macrophages M2, T cells regulatory (Tregs) and T cells follicular helper were lower.…”
Section: Resultsmentioning
confidence: 99%
“…Studies had shown a strong connection between asthma and the immune microenvironment. 25 , 26 Consequently, we next used the GSE41861 database in the Cibersort package to predict the proportion of 22 immune infiltrating cells in the immune microenvironment of asthma. The results are shown in Figure 8A , the percentages of dendritic cells activated, plasma cells, T cells CD4 memory activated and mast cells activated in asthma were higher than controls, while macrophages M2, T cells regulatory (Tregs) and T cells follicular helper were lower.…”
Section: Resultsmentioning
confidence: 99%